International Research Collaboration and International Research Orientation: Comparative Findings About European Academics - Kwiek, Marek (My University, 2018)
In this study, international research collaboration (IRC) and international research orientation (IRO) have been studied at the micro-level of individual academics from the university sector (N = 8,466, 11 European systems). Both were studied crossnationally, cross-disciplinarily, and cross-generationally. This study differs from most existing internationalization literature in its sample (Europe) and focus (patterns of internationalization in research), using more standard methods (a multivariate model approach). It addresses questions about the patterns of IRC and IRO, international publishing, and the predictors of IRC, or what makes some European academics more prone to collaborating with international colleagues in research than others. In the context of changing incentive and reward systems in European academic science, which are becoming more output oriented, it is ever more important for individual academics to cooperate internationally (as well as to co-publish internationally). “Internationalists” increasingly compete with “locals” in university hierarchies of prestige and for access to project-based research funding across Europe. Evidence is presented that co-authoring publications internationally is still a rare form of research internationalization in Europe (50.8% of academics co-author publications internationally). However, as compared with other world regions, the percentage of European academics collaborating internationally in research (63.8%) is very high. A striking cross-national differential within the youngest European generation of academics was found, which may be a strong barrier to intra-European research collaboration in the future.
Keywords: Stratification in science; European academics; internationalists and locals; internationalization of research; cross-national publishing patterns; multivariate model approach; predictors of research collaboration; international research collaboration; international research orientation; research internationalization; research collaboration; collaborative research; scientific collaboration; collaborative science